High titers of infectious SARS-CoV-2 in corpses of patients with COVID-19. (April 2023) - Saitoh, Hisako; Sakai-Tagawa, Yuko; Nagasawa, Sayaka; Torimitsu, Suguru; Kubota, Kazumi; Hirata, Yuichiro; Iwatsuki-Horimoto, Kiyoko; Motomura, Ayumi; Ishii, Namiko; Okaba, Keisuke; Horioka, Kie; Abe, Hiroyuki; et al.
Highlights: Infectious SARS-CoV-2 remained in 55% (6/11) corpses and 43% (13/30) specimens. The highest infectious titer was 2.09E + 06 plaque-forming units/g in corpse lung tissue. The time from death to discovery was 0-1 day in all cases with the infectious virus. The longest postmortem interval with virus infectivity was 13 days (12 days refrigerated). The status of the corpse influences SARS-CoV-2 infectivity. Abstract: Objectives: The prolonged presence of infectious SARS-CoV-2 in deceased patients with COVID-19 has been reported. However, infectious virus titers have not been determined. Such information is important for public health, death investigation, and handling corpses. The aim of this study was to assess the level of SARS-CoV-2 infectivity in the corpses of patients with COVID-19. Methods: We collected 11 nasopharyngeal swabs and 19 lung tissue specimens from 11 autopsy cases with COVID-19 in 2021. We then investigated the viral genomic copy number by real-time reverse transcription-polymerase chain reaction and infectious titers by cell culture and virus isolation. Results: Infectious virus was present in six of 11 (55%) cases, four of 11 (36%) nasopharyngeal swabs, and nine of 19 (47%) lung specimens. The virus titers ranged from 6.00E + 01 plaque-forming units/ml to 2.09E + 06 plaque-forming units/g. In all cases in which an infectious virus was found, the time from death to discovery was within 1 day and the longest postmortem interval was 13 days. Conclusion: The corpses of patients with COVID-19 may have high titers of infectious virus after a long postmortem interval (up to 13 days). Therefore, appropriate infection control measures must be taken when handling corpses.